Recent Advances in Single‐Atom Catalysts for Photoelectrocatalytic Water Splitting - Jiao Yang; Xiaoyang Zheng; Syed Shoaib Ahmad Shah; Chao Wang; Xueyao Li; Zhishuo Yan; Lishan Peng (Carbon Energy)
ABSTRACT Hydrogen is a highly promising energy carrier because of its renewable and clean qualities. Among the different methods for H2 production, photoelectrocatalysis (PEC) water splitting has garnered significant interest, thanks to the abundant and perennial solar energy. Single‐atom catalysts (SACs), which feature well‐distributed atoms anchored on supports, have gained great attention in PEC water splitting for their unique advantages in overcoming the limitations of conventional PEC reactions. Herein, we comprehensively review SAC‐incorporated photoelectrocatalysts for efficient PEC water splitting. We begin by highlighting the benefits of SACs in improving charge transfer, catalytic selectivity, and catalytic activity, which address the limitations of conventional PEC reactions. Next, we provide a comprehensive overview of established synthetic techniques for optimizing the properties of SACs, along with modern characterization methods to confirm their unique structures. Finally, we discuss the challenges and future directions in basic research and advancements, providing insights and guidance for this developing field.